THE STRATEGIC SIGNIFICANCE OF DEVELOPING LEARNER AUTONOMY IN FOREIGN LANGUAGE EDUCATION (Journal of Universal Science Research, 2025)
This paper explores the theoretical and practical foundations of developing learner autonomy in foreign language education. It investigates modern teaching approaches such as task-based and project-based learning, as well as the impact of digital technologies in fostering self-directed learning. The development of autonomy not only supports linguistic proficiency but also promotes critical thinking, self-regulation, and lifelong learning competencies.